2010
DOI: 10.1016/j.joca.2010.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Changes of human menisci in osteoarthritic knee joints

Abstract: Although the expression of major matrix components was markedly enhanced, matrix synthesis was enhanced only modestly, and the changes of matrix in human OA menisci were rather modest in the non-degenerated areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 43 publications
4
41
0
Order By: Relevance
“…The increased Safranin O staining with meniscus aging could represent a shift from a fibroblastic to chondrocytic phenotype during early degeneration and warrants further investigation. Our results along with biochemical data published by Herwig and Adams [15, 57] as well as gene expression studies [59] provide evidence for an accumulation of water-binding proteoglycans in aging and degenerating human menisci and these changes suggest an attempt at adaption or regeneration of the menisci [56, 58]. …”
Section: Discussionsupporting
confidence: 76%
“…The increased Safranin O staining with meniscus aging could represent a shift from a fibroblastic to chondrocytic phenotype during early degeneration and warrants further investigation. Our results along with biochemical data published by Herwig and Adams [15, 57] as well as gene expression studies [59] provide evidence for an accumulation of water-binding proteoglycans in aging and degenerating human menisci and these changes suggest an attempt at adaption or regeneration of the menisci [56, 58]. …”
Section: Discussionsupporting
confidence: 76%
“…The pathologic changes in the menisci in both aging and OA have similarities to changes noted in the articular cartilage, including matrix disruption, fibrillation, cell clusters, calcification and cell death (47, 48). There is significant correlation between gross morphologic changes of OA in the knee cartilage and those in the menisci from the same joints (48).…”
Section: Meniscus and Ligamentsmentioning
confidence: 91%
“…ACLT also resulted in GAG loss in the patellar cartilage that did not improve with Dex or Av-Dex treatment. Similar to articular cartilage, mechanical injuries can also alter the meniscus biomechanical properties, cause disorganisation of collagen network, tissue calcification and concomitant changes in GAG and collagen content (Katsuragawa et al , 2010; Kwok et al , 2014; Pauli et al , 2011; Sun et al , 2012). It was found that the changes in meniscus mechanical properties accompanied changes in the articular cartilage post ACLT; a significant loss (by almost a factor of two) of equilibrium and dynamic compressive stiffness in meniscus from the ACLT knee was observed at week 9, which is consistent with previous studies (Levillain et al , 2015).…”
Section: Discussionmentioning
confidence: 99%